Dampak Tax Amnesty Terhadap Pelaku UMKM di Kabupaten Sidoarjo: The Impact of Tax Amnesty on MSME Actors in Sidoarjo Regency - Nirwana, Nihlatul Qudus Sukma (Journal of Accounting Science, 2018)
This study aims to 1) To analyze interpretively the impact of the implementation of tax amnesty on MSMEs in Sidoarjo district. 2) To analyze and follow up the monitoring and evaluation model of the Tax Amnesty against MSME Actors in Sidoarjo Regency. The research subjects were MSME actors who performed Amnesty Taxes. The technique of collecting data uses In Depth Interview, Literature Study, Documentation. The technique of analyzing data uses qualitative data which is demonstrated by Focus Group Discussion (FGD). From the results of the study there are (1) negative impacts obtained: (a) weakening tax administration and reducing state revenues, (b) increasingly widening the income distribution gap, (c) creating social and racial jealousy, (d) the perception that Indonesia is a failed country because unable to enforce the rule of law in his own country. Whereas Dapak is positively obtained (a) Increasing state income, (b) Giving birth to new tax objects, (c) Secrets of taxpayers participating in the tax amnesty guaranteed security, (d) Increasing the growth of the property industry in the country, (e) Tax elimination that should be owed (f) Improve taxpayer compliance. (2) there are still many MSME actors in Sidoarjo who do not carry out Tax Amnesy because the public is afraid that in relation to the reduced profits (3) there is a lack of socialization and simulation of tax amnesty carried out by the government.